Successful reduced‐intensity stem cell transplantation for GATA2 deficiency before progression of advanced MDS. (8th January 2016) - Saida, Satoshi; Umeda, Katsutsugu; Yasumi, Takahiro; Matsumoto, Akane; Kato, Itaru; Hiramatsu, Hidefumi; Ohara, Osamu; Heike, Toshio; Adachi, Souichi
Abstract: A 13‐yr‐old boy bearing lymphedema and congenital deafness had distinct hematological abnormalities consisting of reduced monocytes, B cells, and dendritic cells in the peripheral blood as well as MDS with normal karyotype in the bone marrow. The patient was diagnosed with Emberger syndrome by sequencing of GATA2 DNA, and underwent RIST from an HLA‐matched unrelated donor. Prompt engraftment and immunological reconstitution were observed without any severe RRT. As most patients with GATA2 anomaly died due to the development of AML or active infections, RIST could be a promising treatment option before progression of advanced MDS.